Antimicrobial properties of Weissella cibaria strains isolated from Campos Das Vertentes, Minas Gerais, Brazil and its potential use as probiotics and bacteriocins producers - Teixeira, Camila Gonçalves (2022)
The genus Weissella is composed of bacteria belonging to the group known as lactic acid bacteria (LAB), are autochthonous to both dairy and non-dairy environments and many strains can produce various compounds of interest to the food industry. This work began with deep research regarding the use of Weissella strains for the food and pharmaceutical industry and the probiotic potential of this genus. A large number of scientific studies reported and support the use of Weissella strains in this field due to their health-promoting properties and technological features for the food industry. This work continues with the study of the biodiversity of Weissella strains isolated in the regions producing artisanal cheeses in Brazil. For this, the analysis of PFGE and Rep- PCR was carried out and it was observed that each study region represents a specific ecological niche. After, the antimicrobial potential of some representative strains was analyzed against the most common foodborne pathogens. Most of the isolates tested showed good inhibition of the pathogens. Also, the technological potential of thirteen strains was evaluated. Some strains showed positive results for most of the tests performed. After, three strains with good inhibitory activity were selected. The genomes ware sequenced and assembled. With the first strain, Weissella cibaria W25 has carried out a comprehensive and comparative genomic analysis with W. cibaria 110, known to pro-duce the weissellicin 110 bacteriocin, and four other non- bacteriocin-producing W. cibaria strains. The analyses showed that the strain W25 has its unique protein cluster genes which can be related to bacteriocins genes indicated by AntiSmash, confirming the possibility of producing two different bacteriocins. Based on these results the genome of the three selected strains was deeply analyzed. The presence of genes for secondary metabolites was investigated and they have a common region in the genome with a putative bacteriocin identified as Bacteriocin_IIc. This putative bacteriocin has no similarity with other bacteriocins from the genus Weissella so far described. Finally, the safety of using these three strains for humanand/or animal consumption and their capacity to be used as probiotics were analyzed. All three strains have no acquired antimicrobial resistance genes and no mobile elements in the genome. W. cibaria strains were resistant to vancomycin which is intrinsic to this genus, had no hemolytic activity, and no one of the known virulence factors was detected. They possess the defense system CRISPR-Cas. Besides they didn’t present any inflammation or cytotoxicity capacity. W. cibaria W21 demonstrates excellent results of adhesion to intestinal cells and exclusion of S. aureus MRSA SA1. However, none of the three strains survived completely through the simulated gastrointestinal tract, but some protective ways can be further studied. In conclusion, this work allowed us to understand the diversity and distribution of Weissella species in different regions producing artisanal cheeses in Brazil. It also showed that some of them have a favorable technological and safety potential for future uses in the food industry or as a probiotic culture. Keywords: Weissella. Technological properties. Antimicrobial activity. Bacteriocins.